Czym jest dziś czytanie literatury? Ankieta - Iwasiów, Inga (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
According to Inga Iwasiów, today’s literature functions as a product (we read pop culture), reading is marketed and comes in a package with an interesting manproduct, namely the writer. At the same time, reading clubs are formed, not only in institutions, but also private ones — their members read and discuss books, just as it was done in the nineteenth and twentieth centuries. Like any academic specializing in Polish literature, the author wants reading to be a necessity for everyone — a sophisticated literary man is better able to understand the world, history and current processes.